PENGARUH INOVASI PRODUK DAN BRAND IMAGE TERHADAP MINAT BELI: (Studi Pada Konsumen Wild Original di Kota Majalengka) - Deni Istiono; Nining Kurniasih (JURNAL AKUNTANSI DAN SISTEM INFORMASI, 2022)
This study aims to determine how the influence of Product Innovation and Brand Image on Buying Interest in Wild Original in Majalengka City. This research is a survey research research using descriptive and verification approaches. The population in this study were Wild Original consumers in Majalengka City with a total sample of 100 respondents. The sampling technique used was Nonprobability Sampling. The data collection technique in this study was a questionnaire using a Likert scale. Data analysis using classical assumption test, multiple regression analysis, coefficient of determination, model feasibility test and partial hypothesis testing. The results showed that Product Innovation was in a good category and Brand Image was in a good category. Hypothesis test results show partially that Product Innovation has a positive and significant effect on Purchase Intention. Brand Image has a positive and significant effect on Purchase Interest.